Pengenalan Budaya Tiongkok Melalui Pembelajaran Bahasa Mandarin untuk Meningkatkan Kompetensi Lintas Budaya Siswa SMK Tana Toraja, Sulawesi Selatan - Azizah, Mir’ah (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
This community service was motivated by the need to improve the cross-cultural competence of vocational school students so they can adapt to global demands, particularly in the context of interaction with Chinese culture, which is increasingly dominant in the tourism and creative economy sectors. The main objective of this service was to strengthen students' understanding of Chinese culture and cross-cultural communication skills through an Asset-Based Community-Driven Development (ABCD) approach that emphasizes the use of local school assets as a foundation for capacity building. The service methods included asset mapping, participatory training, interactive practice, and pre-post evaluation to measurably see improvements in student competency. The results of the service showed significant improvements in cultural understanding, active student participation, and their ability to integrate Chinese cultural values ​​into learning situations and tourism service simulations. Correlation analysis also confirmed a strong relationship between the level of student engagement and their learning outcomes. The conclusion of this service is that the ABCD approach is effective in building relevant, participatory, and meaningful cultural learning for vocational students. The main contribution of this activity lies in strengthening students' multicultural readiness and providing a service model that can be replicated in other vocational education contexts in Indonesia.